SENSORY EVALUATION AND CHEMICAL CHARACTERISTIC OF CATFISH (Pangasius hypophthalmus) MEATBALL MADE OF DIFFERENT HANDLED RAW MATERIAL - Antoni, Muhammad Zaid; Sari, N. Ira; ', Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was purposed to evaluate the sensory and chemical characteristic of catfish (Pangasius hypophthalmus) meatball made of different handled raw material, namely: fresh fish meat, refrigerated fish meat and frozen fish meat. The research methodology used was experimental and composed as non factorial completely randomized design (CRD). The parameters used were sensory value (appearance, odor, taste and texture), proximate chemical composition (moisture, protein and fat), and the value folding test. The result showed that the different raw material handling was significantly affected to all parameters. The best treatment was the using of fresh fish meat as the raw material of catfish (Pangasius hypophthalmus) meatball. It was characteristically appeared circle uniform, without hollow space, and cream white color (7,68), disputrid, characteristically specific fish meatball odor (7,76), characteristically, fish tasted (7,88), solid, compact and elastic texture, (8,12), and folding test criteria was not broken when folded at half and quarter circle (4,73). The fish meatball contained moisture 32, 85%, protein 28,17%, fat 7,96% and ash 8,03 %.Keyword: catfish, refrigeration, freezing, fishball